Generalized Enriched Nonexpansive Mappings and Their Fixed Point Theorems - Rahul Shukla; Rekha Panicker (Abstract and Applied Analysis, 2023)
This paper introduces a novel category of nonlinear mappings and provides several theorems on their existence and convergence in Banach spaces, subject to various assumptions. Moreover, we obtain convergence theorems concerning iterates of α-Krasnosel’skiĭ mapping associated with the newly defined class of mappings. Further, we present that α-Krasnosel’skiĭ mapping associated with b-enriched quasinonexpansive mapping is asymptotically regular. Furthermore, some new convergence theorems concerning b-enriched quasinonexpansive mappings have been proved.